2019
DOI: 10.1002/cmdc.201900397
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Bisphosphonates: Ionic Liquids and Organic Salts from Zoledronic Acid

Abstract: Novel ionic liquids and organic salts based on mono-o rd ianionic zoledronate and protonated superbases, choline and nalkylmethylimidazolium cations, were prepared and characterized by spectroscopic and thermal analyses. Most of the prepared salts display amorphous structures and very high solubility in water and saline solutions, especially the dianionic salts. Amongt he zoledronate-basedi onic compounds, those containing choline [Ch] and methoxyethylmethylimidazolium [C 3 OMIM] cations appear to have signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…For the last 12 years, organic salts and ionic liquids (OSILs) from active pharmaceutical ingredients (APIs), or simply API-OSILs [14][15][16][17][18][19][20][21][22], have been studied at the academic level [14,18,19,[23][24][25]. Ionic liquids (ILs) are salts with melting points below 100 • C (some of them are liquid at room temperature) that result from the pairing of organic cations with organic and inorganic anions [14,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…For the last 12 years, organic salts and ionic liquids (OSILs) from active pharmaceutical ingredients (APIs), or simply API-OSILs [14][15][16][17][18][19][20][21][22], have been studied at the academic level [14,18,19,[23][24][25]. Ionic liquids (ILs) are salts with melting points below 100 • C (some of them are liquid at room temperature) that result from the pairing of organic cations with organic and inorganic anions [14,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of protonated organic superbases (1,1,3,3-tetramethylguanidinium [TMGH] and 1,5-diazabicyclo(4.3.0)non-5-enium [DBNH]) and quaternary ammonium (cholinium [Ch] and 1-(2-hydroxyethyl)-3-methyl-1H-imidazol-3-ium [C 2 OHMIM]) cations relied on the known information about their biocompatibility [15,23]. Despite their low toxicity, the combination of these cations with other APIs has rendered highly active API-OSILs in the past, in particular antimicrobial and anti-tumoral [19,20,22]. The preparation of compounds 1-4 consisted of the addition of the diluted superbases to a dispersion of ALN (pathway A).…”
Section: Synthesis and Characterization Of Aln-osilsmentioning
confidence: 99%
“…In all cases, the 1 H NMR spectra showed that the cation/anion The preparation of compounds 1-4 consisted of the addition of the diluted superbases to a dispersion of ALN (pathway A). These particular compounds, termed Superionic Liquids of APIs, were prepared according to a previous methodology reported by us for zoledronic acid [22] as well as other APIs [16]. While both monoanionic ALN-OSILs were obtained as solids, the two dianionic were isolated as pastes.…”
Section: Synthesis and Characterization Of Aln-osilsmentioning
confidence: 99%
See 2 more Smart Citations